Synergetic Effects of Plasmodium, Hookworm, and Schistosoma mansoni Infections on Hemoglobin Level among Febrile School Age Children in Jawe Worda, Northwest Ethiopia - Tadesse Hailu; Mulat Yimer; Wondemagegn Mulu; Bayeh Abera (Journal of Parasitology Research)
Plasmodium coinfection with hookworm and/or Schistosoma mansoni has detrimental effects on human’s hemoglobin level. This study aimed to determine the effects of plasmodium, hookworm, and S. mansoni infections on hemoglobin level among febrile school age children in Northwest Ethiopia. A cross-sectional study was conducted from April 2016 to August 2016. Plasmodium and helminths infections were detected using Giemsa stain and formol-ether concentration techniques, respectively. Hemoglobin level was determined using Hemocue method. Among 333 children, 143 (42.9%), 49 (14.75%), and 22 (6.6%) had Plasmodium, hookworm, and Schistosoma mansoni infections, respectively. The prevalence of Plasmodium-hookworm and Plasmodium-Schistosoma mansoni coinfections was 18 (12.6%) and 4 (2.8%) in children, respectively. The overall prevalence of anaemia in children was 41.4%. Effect of Plasmodium, hookworm, and Schistosoma mansoni on hemoglobin level was high. Therefore, febrile children should be screened for Plasmodium, hookworm, Schistosoma mansoni, and anaemia simultaneously in malaria endemic areas.